Students' Perception of the Criminalization of Cohabitation (Kumpul Kebo) in Indonesia: From Quantitative to Normative Analysis - Hafrida, Hafrida; Haryadi, Haryadi; Munandar, Tri Imam; Rakhmawati, Dessy; bt Ab. Kadir, Noor Aida (Jambe Law Journal, 2024)
Living together as unmarried partners, commonly known as cohabitation or “kumpul kebo” in Indonesia, was not prohibited under the old Indonesian Criminal Code (KUHP). However, in light of Indonesia’s cultural emphasis on decency, cohabitation has recently been criminalized. According to Article 412 paragraph (1) of the New KUHP, cohabitation is now considered a criminal offense, punishable by a maximum fine of thirty million rupiahs and imprisonment for up to six months. This legal development sparked significant reactions among university students, who voiced their concerns during protests against the New KUHP. Debates continue regarding the legality of cohabitation, prompting this study to investigate the perception among students in Jambi Province regarding its criminal status. The findings indicate that 55.3% of the 340 respondents from local universities believe cohabitation should not be illegal. They argue that ethical considerations are more pertinent, suggesting that societal and moral sanctions against offenders suffice. Those who contest such views may resort to customary law for civil proceedings against offenders they deem to have transgressed societal norms